Кримські татари - національна меншина чи корінний народ? - Вітман, К.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Статья концентрируется на проблемах Крымской автономии, в частности детально исследуется конфликтогенныш потенциал крымско-татарского фактора. Автор анализирует обоснованность претензии крымских татар на статус коренного народа. Также отслеживается тенденция эволюции претензий этноса от земельных требований до трансформации административно-территориальной автономии в автономию крымско-татарского народа. The article is devoted to the problems of Crimea autonomy, conflict potential of Crimean Tatar factor is investigated in particular. The author analyses whether Crimean Tatar claims to get indigenous people status are founded. The tendency of Crimean Tatar claims evolution from land claims to claims of transformation of territorial autonomy into national one is tracked.